Epigenetic control of plant senescence and cell death and its application in crop improvement - Zhang, Yu; Huang, Dongmei; Miao, Ying (Frontiers in Plant Science, 2023)
Plant senescence is the last stage of plant development and a type of programmed cell death, occurring at a predictable time and cell. It involves the functional conversion from nutrient assimilation to nutrient remobilization, which substantially impacts plant architecture and plant biomass, crop quality, and horticultural ornamental traits.In past two decades, DNA damage iwas believed to be a main reason for cell senescence. Increasing evidence suggests that the alteration of epigenetic information is a contributing factor to cell senescence in organisms. In this review, we summarize the current research progresses of epigenetic and epitranscriptional mechanism involved in cell senescence of plant，, in at the regulatory level of DNA methylation, histone methylation and acetylation, chromatin remodeling, non-coding RNAs and RNA methylation. Furthermore, we discuss their molecular genetic manipulation and potential application in agriculture for crop cell senescenceimprovement., Finally we finally gave point out perspective the prospects of future research topics.